Different Neural Mechanisms Underlie Deficits in Mental Flexibility in Post-Traumatic Stress Disorder Compared to Mild Traumatic Brain Injury - Pang, Elizabeth W. (Frontiers in Psychiatry, 2015)
Mental flexibility is a core executive function that underlies the ability to adapt to changing situations and respond to new information. Individuals with PTSD and mTBI complain of a number of executive function difficulties, one of which is mental inflexibility or an inability to switch between concepts. While the behavioural presentation of mental inflexibility is similar in those with PTSD or mTBI, we hypothesized that the differences in their etiology would manifest as differences in their underlying brain processing. The neural substrates of mental flexibility have been examined with a number of neuroimaging modalities. Functional magnetic resonance imaging (fMRI) has elucidated the brain regions involved while electroencephalography (EEG) has been applied to understand the timing of the brain activations. Magnetoencephalography (MEG), with its high temporal and spatial resolution, has more recently been used to delineate the spatiotemporal progression of brain processes involved in mental flexibility and has been applied to the study of clinical populations. In a number of separate studies, our group has compared the source localization and brain connectivity during a mental flexibility set-shifting task in a group of soldiers with PTSD and civilians with an acute mTBI. In this paper, we review the results from these studies and integrate the data between groups to compare and contrast differences in behavioural, neural and connectivity findings. We show that the different etiologies of PTSD and mTBI are expressed as distinct neural profiles for mental flexibility that differentiate the groups despite their similar clinical presentations.